Evaluating Challenges and Opportunities Associated with Cloud-Based Big Data Solutions - Ковачева, Марияна (Научни трудове, 2025)
Everyday large amounts of data are generated through different devices – from the smallest sensors to all smart technologies. All types of data are produced and to be used, it needs to be evaluated, categorized and stored. This article examines opportunities offered by cloud-based Big Data solutions which include real-time analytics, integration with different technologies, available on-demand computing resources and services, which make it possible to analyse in an effective and simple way the large amounts of different types of data. Also challenges connected to cloud-based Big Data solutions for companies and industries are presented and considered.
Keywords: Големи данни; Облачни изчисления; Обработка на информация в реално време